Cavitation induction by projectile impacting on a water jet. (May 2019) - Stavropoulos Vasilakis, E.; Kyriazis, N.; Koukouvinis, P.; Farhat, M.; Gavaises, M.
Highlights: Immersed Boundary Method coupled with multiphase flow solver accounting cavitation. Cavitation structures unveiled upon solid projectile impact on water jet. Shock-wave and vapour structures intensified by higher flow blockage. Richtmyer–Meshkov instability caused by shock interaction with liquid–gas interface. Abstract: The present paper focuses on the simulation of the high-velocity impact of a projectile impacting on a water-jet, causing the onset, development and collapse of cavitation. The simulation of the fluid motion is carried out using an explicit, compressible, density-based solver developed by the authors using the OpenFOAM library. It employs a barotropic two-phase flow model that simulates the phase-change due to cavitation and considers the co-existence of non-condensable and immiscible air. The projectile is considered to be rigid while its motion through the computational domain is modelled through a direct-forcing Immersed Boundary Method. Model validation is performed against the experiments of Field et al. (2012), who visualised cavity formation and shock propagation in liquid impacts at high velocities. Simulations unveil the shock structures and capture the high-speed jetting forming at the impact location, in addition to the subsequent cavitation induction and vapour formation due to refraction waves. Moreover, model predictions provide quantitative information and a better insight on the flow physics that has not been identified from the reported experimental data, such as shock-wave propagation, vapour formation quantity and induced pressures. Furthermore, evidence of the Richtmyer–Meshkov instability developing on the liquid–air interface are predicted when sufficient dense grid resolution is utilised.